Obesity, diabetes mellitus, arterial hypertension and the risk of endometrial cancer - Sobczuk, Anna; Wrona, Marcin; Sobotkowski, Janusz; Szymczak, Wiesław; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
Aim of study: The purpose of our study was to evaluate the frequency of obesity, arterial hypertension and diabetes mellitus in women with endometrial cancer. We also compared weight at young age, weight gain during adulthood, present weight and height in women with endometrial cancer and without cancer. Materials and methods: The data were obtained in a hospital-based case-control study of 125 women with histologically confirmed endometrial cancer (cases) and 135 women who were admitted for gynaecological, non-neoplastic, non-hormone-related conditions (controls). Results: The mean BMI (kg/m2) was significantly higher in women with endometrial cancer than in controls (29.2 vs. 27.6; p<0.05). The mean weight was also higher in patients with cancer (75.1 kg vs. 71.6 kg; p<0.05). We observed no differences between groups in present height and weight at 25. Weight gain during the last 10 years was observed significantly more often in women with cancer. The value of weight gain was also higher in women with cancer (p<0.001). Arterial hypertension, diabetes mellitus and ischaemic heart disease occurred significantly more often in women with endometrial cancer. Conclusions: Obesity, weight gain during adulthood, arterial hypertension and diabetes mellitus are associated with elevated risk of endometrial cancer. Weight loss (diet, physical activity), treatment of coexisting arterial hypertension and diabetes markedly reduce the relative risk of endometrial cancer in peri- and postmenopausal women.